Na ausência do calor do encontro : as significações sobre a prática pedagógica e a participação das crianças no contexto da pandemia por Covid-19 - Melo, Sandra Cristina de (2021)
This research makes up the umbrella project, entitled “The construction of social knowledge by children: study on children's experiences and meanings” (2016-2020), of the Research Group in Childhood Psychology, linked to the Graduate Program in Education at UFMT. This is an investigative exercise (2019-2021), which aims to identify and analyze the representational contents that guide the reconfiguration of educational practices implemented in education, mediated by technology, in the emergency context of the coronavirus pandemic. The participation category will guide the analysis of the information because it is understood that this element enables us to think about the social status of the child in the schooling process. The theoretical references adopted assume the psychosocial perspective of the Theory of Social Representations of Moscovici (1078, 2010, 2012); Jodelet (1989, 2001, 2005, 2007); Jovchelovitch (2008); Marková (2006,2017); Abric (1998) and Campos (2003,2017). To discuss the importance of social practices in the construction of children's knowledge, we articulated the studies of Gilly (2001), Chombart De Lauwe (1991), Gibson (1986), Brougére (2004) and Duveen (1995, 1986). On the historicity of the Social Status of the Child, we build with Ariès (1981), Kuhulmann Jr. (1998, 2002,2004), Postman (1999), Charlot (1979, Kramer (1995, 2006), Qvotrup (2014), Abramowicz (2016) and Sarmento (2011,2017). As for educational practices, we referenced Arroyo (2014) and Vygotski (2009,2010,2018). The debate about children's participation in the school scene is based on the studies of Marková (2006,2017), Arnstein (1969), Arent(1957), Hart (1992), Thomas (2007) Shier (1999) Comenius,( 2006), Tomas(2007), Tisdall and Punch(2001) Zittoun (2014) James (1998), Postman(1999)and OliveiraFormosinho (2015, 2017,2019) Paulo Freire(1983). As for remote education, the contribution is in Freitas et al. (2019), Santos, Carvalho, and Pimentel (2010), Henrique(2020), Machado(2020), Saraiva, Lockman(2020), Martins and Almeida(2020) and Cunha (2020). The data production was carried out with a group of seven children, four boys and three girls, aged 6 to 7 years, from a first-year class of elementary school, belonging to a public school in Cuiabá-MT. The children's parents and the teacher responsible for the class also participated in this study. The methodology is characterized by its qualitative nature, aligned with the assumptions of the single case study, qualified by Marková (2017) as a study that is based on the interactive epistemology, in which the subjects of knowledge share a lived situation and, in turn, influence and are influenced by each other. The study involved two stages: participant observation with the school group during the educational process carried out in the WhatsApp group and semi-structured interviews with the children, parents, and the teacher. For the analysis and processing of the information, the comprehensive analysis was adopted as a procedure. The analysis of these interactions, in their singularity, constitutes the guiding axis of this research, dedicated to understanding how the interactions happen, the social dynamics of the group in the context of remote emergency education, when parents, children and teachers are called to rebuild social practices related to educational processes regarding communication and to situate themselves in a participatory manner in the school context.